Spontaneous coronary artery dissection, fibromuscular dysplasia, and biventricular stress cardiomyopathy: a case report. Issue 4 (25th March 2022) - Blazak, Penni L; Holland, David J; Basso, Thomas; Martin, Josh
Abstract: Background: Spontaneous coronary artery dissection (SCAD) is an important cause of acute coronary syndrome and is associated with fibromuscular dysplasia (FMD). The diagnosis of stress cardiomyopathy in patients with SCAD and FMD is uncommon, though an important consideration given the shared risk profile. Complications of severe left ventricular (LV) dysfunction associated with stress cardiomyopathy, such as LV thrombus, complicate the management of SCAD where anticoagulation is controversial in the context of SCAD-associated intramural haematoma. Case summary: A 65-year-old female presented with non-ST elevation myocardial infarction with a recent diagnosis of hypertension but no other traditional cardiovascular risk factors. There was, however, a family history of early cardiac death from myocardial infarction affecting her mother. Echocardiography demonstrated severe biventricular dysfunction with circumferential akinesis of the mid to apical segments. Coronary angiography demonstrated type 2A SCAD involving the first diagonal artery. Cardiac magnetic resonance imaging (MRI) confirmed a diagnosis of stress cardiomyopathy with biventricular involvement, complicated by LV apical thrombus and a focal region of myocardial infarction. Vascular imaging confirmed the presence of FMD. Guideline-directed heart failure therapy in addition to clopidogrel and rivaroxaban was prescribed. Follow-up contrast echocardiography at six-weeks confirmed resolution of LV dysfunction and resolution of the LV thrombus with no adverse events. Discussion: The dual diagnosis of SCAD and stress cardiomyopathy is uncommon. Cardiac MRI was useful for confirming the diagnosis of stress cardiomyopathy and the presence of LV thrombus, where anticoagulation may complicate the management of intramural haematoma in patients with concomitant SCAD and FMD.